Inquiry-Based Chemistry Learning: An Effective Strategy to Strengthen Students' Conceptual Understanding - Khasanah, Khasanah; Dewimarhelly, Dewimarhelly (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This study aims to determine whether inquiry-based chemistry learning has an effect on students' conceptual understanding, especially on colloid material, by comparing learning outcomes before and after the application of inquiry-based learning. Methodology: The study used a one-group pretest-posttest weak experimental design, purposive sampling technique with a sample of 40 students, instruments in the form of multiple-choice tests and questionnaires. Data analysis used the Liliefors normality test, Fisher's homogeneity test, t-test, and N-Gain quantitatively. Main Findings: The results of the study showed an increase in students' conceptual understanding after inquiry-based learning, with the average score increasing from pretest to posttest. The N-Gain value of 0.46 is included in the moderate category, dominated by the moderate category. Statistical tests showed that t count > t table, indicating a significant effect of inquiry-based learning. Novelty/Originality of this study: This study emphasizes specific conceptual understanding in inquiry-based chemistry learning on colloids. The novelty lies in the empirical evidence of direct classroom implementation, which demonstrates how a structured inquiry process can significantly improve students' conceptual construction, resulting in moderate improvement.